MANAJEMEN PESERTA DIDIK DALAM MEMBENTUK KARAKTER SISWA AGAMIS PADA MAN 2 TABALONG - Akhmad Alwi; Hidayatullah, Muhammad Hermansyah, Muhammad Diky Wahyudi, Muhammad Hudriyuddin, Syahrani (Jurnal Salome : Multidisipliner Keilmuan, 2023)
This research aims to determine student management in forming the character of religious students at MAN 2 Tabalong. This research uses quantitative methods with data collection techniques using questionnaires. The respondents in this research were students and teachers at MAN 2 Tabalong, totaling 60 students and 50 teachers. The results of the research show that participant management has a positive and significant effect on the character formation of religious students at MAN 2 Tabalong. This shows that good student management can help shape the character of religious students. Therefore, it is recommended that schools can improve student management in forming the character of religious students by providing training and development to teachers and school staff, as well as involving parents in the process of forming the character of religious students.